A new species and distribution records of Dichotomius Hope, 1838 (Coleoptera: Scarabaeidae: Scarabaeinae) in Colombia - Chamorro, William; Lopera-Toro, Alejandro; Rossini, Michele (Zootaxa, 2021)
Dichotomius (Dichotomius) quadrilobatus new species (Coleoptera: Scarabaeidae: Scarabaeinae: Dichotomiini), from western Amazonia (Brazil, Colombia, Ecuador and Peru) is described and its putative systematic position within the Dichotomius boreus species group is discussed. An updated identification key to the species of the Dichotomius boreus species group is provided. Additionally, Dichotomius (Selenocopris) fortepunctatus Luederwaldt, 1923 is recorded for the first time in Colombia.